Investigating the Effects of Augmented Reality on Message Credibility When Visualizing Environmental Impacts - Ferron, Aymeric; Assor, Ambre; Dragicevic, Pierre; Jansen, Yvonne (IEEE transactions on visualization and computer graphics, 2025)
Augmented reality (AR) has increasingly been used to communicate environmental impacts, offering greater engagement than conventional displays. However, its effect on message credibilit-how much people believe in the content of the communication-remains unclear. In a preregistered study, we compared the perceived credibility of environmental information presented via visualizations on an AR headset or a desktop display. We created display-specific visual encodings (3D concrete for AR, 2D bar charts for desktop) and added two control conditions to cross display and encoding. We found no difference in message credibility between AR and desktop, though concrete AR was rated most engaging.